'Second-generation' 1, 2, 3-triazole-based inhibitors of Porphyromonas gingivalis adherence to oral streptococci and biofilm formation. Issue 2 (15th January 2019) - Patil, Pravin C.; Tan, Jinlian; Demuth, Donald R.; Luzzio, Frederick A.
Abstract : This study details the design, synthesis and bioassay of 'click' peptidomimetic compounds which inhibit the adherence of P. gingivalis to S. gordonii, a primary step toward pathogenic colonization of the subgingival pocket. Abstract : Several 'second-generation' click inhibitors of the multi-species biofilm propagated by the adherence of the oral pathogen Porphyromonas gingivalis to Streptococcus gordonii were synthesized and evaluated. The design of the structures was based on the results obtained with the first-generation diphenyloxazole 'click' inhibitors which bear suitable hydrophobic and polar groups within a dual scaffold molecule bearing a 1, 2, 3-triazole spacer. The structures of the synthetic targets reported herein now consist of a triazolyl(phenylsulfonylmethyl) and a triazolyl(phenylsulfinylmethyl) spacer which joins a 4, 5-diphenyloxazole with both phenyl rings bearing lipophilic substituents. The triazolyl "linker" group is formed by a click reaction between the 4-azido(phenylsulfonyl/sulfinylmethyl) oxazoles and acetylenic components having aryl groups bearing hydrophobic substituents. The 1, 3, 5-trisubstituted-2, 4, 6-triazine scaffold of the most active click compounds were modeled after the structural motif termed the VXXLL nuclear receptor (NR) box. When substituted at the 3- and 5-positions with 2- and 4-fluorophenylamino and N, N -diethylamino units, the candidates bearing the 1, 3, 5-trisubstituted-2, 4, 6-triazine scaffold formed a substantial subset of the second-generation click candidates. Four of the click products, compounds95, 111, 115 and122 showed inhibition of the adherence of P. gingivalis to S. gordonii with an IC50 range of 2.3–4.3 μM and only111 exhibited cytotoxic activity against telomerase immortalized gingival keratinocytes at 60 μM. These results suggest that compounds95, 115, 122, and possibly111 represent the most suitable compounds to evaluate for activity in vivo .